Impact of Packaging as a Marketing Strategy to Counter Increasing Competition - Khalid, Faizan (2010)
This study has been focused on testing the impact of packaging as a marketing strategy to counter increasing competition for companies operating in fast moving consumer goods in Pakistan. The specific area we have discussed in this study is the dairy industry of Pakistan. The dairy industry of Pakistan is going through an evolution stage and packaged milk is gaining more and more importance with the passage of time.